The Global Financial Crisis in Australia - Chesters, Jenny (My University, 2011)
This paper examines the effects of the Global Financial Crisis (GFC) on several dimensions of the day-to-day lives of Australians: changes in total income; changes in usual hours worked; satisfaction with financial position and perceptions of job security. Using longitudinal data collected in Waves 6, 7 and 8 of the Household Income and Labour Dynamics in Australia (HILDA) Survey (n=11061), I find that although the GFC had not impacted upon unemployment nor usual hours worked, retired Australians were less satisfied with their financial position and employed people were becoming concerned about job security.
Keywords: Income & Finance -- Income (Salary and Wages); Employment; Employment -- Security of employment; Income, wealth and finances; Labour market; Employment; Income & Finance; Income (Salary and Wages); Security of employment; Employment and unemployment; Income, wealth and finances